Privacy at Work: A Review and a Research Agenda for a Contested Terrain. (January 2020) - Bhave, Devasheesh P.; Teo, Laurel H.; Dalal, Reeshad S.
Privacy in the workplace is a pivotal concern for employees and employers. Employees expect to be in control of the personal information and access they provide to the organization. Employers, however, expect extensive information regarding their employees as well as extensive access to employees' presence. The chasm between these two often competing expectations has been magnified by regulatory and technological trends. We begin the review by integrating viewpoints from multiple disciplines to disentangle definitions of privacy and to delineate the privacy contexts of information privacy and work environment privacy. We then identify the key stakeholders of privacy in the workplace and describe their interests. This discussion serves as a platform for our stakeholders' privacy calculus model, which in turn provides a framework within which we review empirical findings on workplace privacy from organizational research and related disciplines and from which we identify gaps in the existing research. We then advance an extensive research agenda. Finally, we draw attention to emerging technologies and laws that have far-reaching implications for employees and employers. Our review provides a road map for researchers and practitioners to navigate the contested terrain of workplace privacy.